APPLICATION OF INFORMATION TECHNOLOGY IN EDUCATIONAL MANAGEMENT: CASE STUDY IN SENIOR HIGH SCHOOLS IN INDONESIA - Loso Judijanto; Nur Hakim; Widya Armalia (CV. ADIBA AISHA AMIRA, 2025)
The development of information technology has brought significant changes in educational management, especially at the high school (SMA) level. The application of technology in school administration, learning systems, and communication between stakeholders is considered capable of increasing the efficiency and effectiveness of education management. This research aims to examine the application of information technology in educational management in high schools in Indonesia through a literature review approach. Data sources were obtained from scientific journals, books and relevant research reports to evaluate the benefits, challenges and directions of development of information technology in educational management. The results of the study show that the implementation of information technology has helped schools increase data transparency, the effectiveness of online learning, and the efficiency of academic administration. However, several obstacles are still faced, such as limited technological infrastructure, lack of skills of teaching staff in using technology, and budget limitations in some schools. To optimize the application of information technology in education management, support is needed from the government, schools and stakeholders through the provision of adequate infrastructure, training for teaching staff, and regulations that support the digitalization of education. The implications of this research confirm that information technology has a strategic role in the transformation of educational management in high school. Therefore, further research is needed to explore more effective and sustainable technology implementation models, as well as evaluate the long-term impact of educational digitalization on the quality of learning and school management.